1981
DOI: 10.1007/bf01314437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a virion envelope herpes simplex virus vaccine against experimental skin infections in hairless mice

Abstract: Hairless mice were immunized with herpes simplex virus type 1 (HSV-1) envelope antigen (EAG), EAG in association with polyriboinosinic . polyribocytidylic acid-poly-L-lysine complexed with carboxymethylcellulose (PICLC), and inactivated purified HSV-1 (VAG). After 2 weeks the mice were challenged by a percutaneous HSV-1 infection in the orofacial (OF) or lumbosacral (LS) skin area. Following immunization a consistent cell-mediated immune response was observed in all immunized mice, although the humoral immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…We have recently demonstrated that the vaccine utilized in the present study elicited both humoral and CMI in mice, rabbits and chimpanzees (1, 2, 3) and these observations are also in agreement with others who found similar results after vaccination with subunits vaccine or envelope proteins (5,6).…”
Section: Diseussionsupporting
confidence: 94%
“…We have recently demonstrated that the vaccine utilized in the present study elicited both humoral and CMI in mice, rabbits and chimpanzees (1, 2, 3) and these observations are also in agreement with others who found similar results after vaccination with subunits vaccine or envelope proteins (5,6).…”
Section: Diseussionsupporting
confidence: 94%
“…[Cappel et al, 1978;Cappel et al, 1980;Cappel et al, 19821 as well as in humans [Cappel et al, 1980;Cappel et al, 19821. These observations are also in agreement with others who found similar results after immunization with slightly different subunit vaccines, envelope proteins, or purified glycoproteins [Balachandra et al, 1982;Hilleman et al, 1981;Kitces et al, 1977;Klein et al, 1981;Skinner et al, 19821. In the various animal models studied, we and others reported earlier that these vaccines protected the animals against experimental infection [Capel, 1976;Hilleman et al, 1981;Kitces et al, 19771. In the present study we confirmed that the vaccine elicited the production of various types of specific antibodies as well as CMI in humans.…”
Section: Discussionsupporting
confidence: 93%
“…Stanberry and co-workers [28] reported that both the number of episodes of recurrent disease seen following intravaginal HSV-2 infection of guinea-pigs and their duration, were significantly reduced in animals previously given a mixture of HSV-1 gB and gD with Freund's Complete Adjuvant, compared to control, unimmunized animals. Other workers have reported that subunit HSV vaccines or purified HSV glycoproteins have failed to provide any significant protection against the establishment of latent infection in mice [6,9,19] although injection of one preparation in the presence of the adjuvant polyriboinosinic: polyribocytidylic acid-poly (L-lysine) and carboxymethylcellulose (PICLC) reduced the development of ganglionic infection [29].…”
Section: Discussionmentioning
confidence: 99%